Christian Theological Analysis of Humanoid Technology Development: Perspectives on Imago Dei and Digital Ethics - Widjaja, Budiman; Zalukhu, Amirrudin; Eng, Sam Un (Sekolah Tinggi Teologi Transformasi Indonesia, 2025)
Abstract:The rapid advancement of humanoid technologies and artificial intelligence has raised significant ethical and theological questions, particularly within the Christian context. This study examines the development of humanoid technology through the lens of Christian theology, focusing on the concept of Imago Dei and principles of digital ethics. Drawing on qualitative, literature-based analysis, the research explores how the spiritual, moral, and relational dimensions of humanity cannot be authentically replicated by artificial agents. The study also highlights potential risks associated with humanoid technology, including manipulation, bias, and erosion of human dignity. By integrating theological reflection with digital ethical principles, the research proposes guidelines for responsible design, deployment, and interaction with humanoid systems. Emphasis is placed on preserving human dignity, promoting justice, and ensuring that technological innovation serves the common good. The findings underscore the importance of interdisciplinary collaboration among theologians, ethicists, and technologists to align technological progress with moral and spiritual values. This approach provides a normative framework for ethically coherent and theologically informed humanoid development.